EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) BERBANTUAN AUGMENTED REALITY BANGUN RUANG TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Ristiana, Bunga; Widiyono, Aan (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research was to determine the influence before and after the use of Indonesian Realistic Mathematics Education (PMRI) approach assisted by Augmented Reality spatial structures, and to determine the effectiveness of the use of the Indonesian Realistic Mathematics Education (PMRI) approach assisted by Augmented Reality spatial structures effectively on the mathematics learning outcomes of grade V students of SD Negeri 3 Krasak Pecangaan Jepara. This type of research is a quantitativeresearch with an experimental method with a Pre-Experimental One Group Pretest-Posttest research design. In the T-test, a significant value (2-tailed) of 0.000 was obtained while the α value was 0.05 or 0.0000.05 and the tcountttable or 15.2171.717, then H0 was rejected and Ha was accepted. In the simple linear regression test (F-test) obtained a significant value in the anova table of 0.000α or 0.0000.05, while the Fcount value is 99.120 and Ftable is 4.28 then FcountFtable or 99.1204.28. So it can be concluded that there is an influence before and after the use of Indonesian Realistic Mathematics Education (PMRI) approach assisted by Augmented Reality spatial structures, and the use of the Indonesian Realistic Mathematics Education (PMRI) approach assisted by Augmented Reality spatial structures is effective on the mathematics learning outcomes of grade V students of SD Negeri 3 Krasak Pecangaan Jepara.